Structure and mechanics of native and decellularized porcine cranial dura mater - Ashma Sharma; Jun Liao; Lakiesha N. Williams (Engineered Regeneration, 2023)
The dura mater is the outermost layer of meninges and consists of a dense elastic membrane that keeps cerebrospinal fluid inside the cavity. In most cranial surgical interventions, the dura mater is incised and needs to be repaired with a graft replacement. We assessed decellularized porcine dura mater as a novel graft material by quantifying the mechanical and structural properties of the dura membrane. Porcine dura mater was decellularized using the Sodium Dodecyl Sulfate (SDS) technique and subjected to uniaxial tensile testing, micro indentation testing, histological analysis, and Transmission Electron Microscopy (TEM). For native dura, we found the tensile modulus in the linear region (15%-25% strain) to be 19.31 ± 1.23 MPa, with an initial tensile modulus (0%-3.5% strain range) of 451 ± 0.30 kPa, and the failure stress as 4.61 ± 1.50 MPa at 35% strain. For decellularized dura, the tensile modulus in the linear region was 10.81 ± 0.88 MPa, the initial tensile modulus was 226 ± 22 kPa, and the failure stress was 4.55 ± 1.05 MPa at 55% strain. The effective compressive modulus was 7 to 19 kPa and 19–57 kPa for the native dura and the decellularized dura, respectively. Our histological and TEM observations showed that the orientation of fibers within the dura was maintained after decellularization. In short, our study demonstrated that decellularized porcine dura was able to maintain its overall morphological/structural integrity and preserve the native dura's mechanical behavior, which provides a solid foundation for its use as a functional grafting material.